Alasan Ketidakpatuhan Inggris terhadap Basel Convention on The Control of Transboundary Movements of Hazardous Wastes Tahun 2007-2019 - Gaffar Mu'aqaffi; Nadia Farabi (Journal of International Relations Diponegoro, 2019)
United Kingdom is a country who illegaly export its electronic waste to developing countries. Despite United Kingdom has ratified the Basel Convention on the Control of Transboundary Movements of Hazardous Waste, United Kingdom is the the most exporter of illegal electronic waste in the European Union. The convention require every states party to treat its electrionic waste ecologically friendly and prohibit exporting its electronic waste to developing countries. This condition can be assumed that United Kingdom does’nt comply the convention which it has ratified in 1994. This research will employ non-compliance theory by Ronald B. Mitchell to explain the cause of United Kingdom non-compliance. Mitchell indentify three kinds of compliance, they are non- compliance due to preference, non-compliance due to incapacity and non-compliance due to inadvertence. The main argument of this research is United Kingdom’s non-compliance caused by its preference. Non-compliance gives United Kingdom benefit economically